Study of Critical Discourse Analysis (CDA) Teun a van Dijk in Jokowi News Sentil Minister Related to Oil Price Increase in Beritasatu.com - Zey Anastasya; Anwar Effendi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The development of the times and technology is giving a big enough influence, especially in the world of information and communication. The existence of information media, both printed and electronic, makes it easier for the public to obtain information and access all circulating news. The public, as recipients of the news or information, must take advantage of the critical thinking process, so that they are able to digest the news they receive until they are close to the truth of the news they enjoy. In line with this statement, this study aims to analyze the news with the headline News on the Increase in Cooking Oil Prices and Pertramax which was published on the beritasatu.com page. This research belongs to the type of descriptive qualitative research. Data collection techniques carried out in this study include documentation techniques, listening techniques, and note-taking techniques. The data analysis technique used in this research is content analysis or content analysis. The object of this research is electronic news on the beritasatu.com page with the news entitled “Jokowi Sentil Menteri Soal Kenaikan Harga Minyak Goreng Dan Pertamax Pada Laman Berita1.com Prices which was published on April 6, 2022. The object of this research was chosen because it has an actual topic, and is still widely discussed. to date. The theory used as the basis for analyzing the data is the theory of critical discourse analysis from Van Dijik's perspective, which includes text, context and social cognition. The results showed that; (1) the topic was raised because the news presenters wanted to present news that seemed to answer some of the questions that existed in the ideology of the community; (2) The meaning shown in the news discourse is to provide information to the public regarding the president's steps in dealing with the problem of rising oil prices and Pertamax; (3) the form of the sentence used is dominated by active sentences and uses a lexicon of foreign language terms; (4) the graphics shown are dominated by graphics in the form of images; (5) Based on the description presented in the news, it can be seen that the news seems to answer the opinion circulating in the community. Regarding the increase in the price of cooking oil and pertamax which are currently circulating